Information sharing and organizational knowledge production in two Finnish firms: an exploration using activity theory - Gunilla Widén-Wulff; Elisabeth Davenport (Information Research: An International Electronic Journal)
Introduction. In this paper, we discuss the link between information sharing and organizational knowledge production in two very different organizations - a company that handles insurance claims and a small entrepreneurial hi-tech company. We suggest that this link has not been adequately addressed by studies of information behaviour, though a number of recent papers (e.g. Wilson, 2005; Bartlett and Toms, 2005) have proposed that human information behaviour research should appropriate methods from workplace studies and CSCW to provide a richer account of organizational information and knowledge work. Method. Two case studies of sharing practices in Finnish firms were carried out. Analysis. The version of activity theory that has been developed by Engeström (1999) and other Finnish researchers (Kuutti, 1996) was used to analyse the data. This has provided highly specific accounts of information sharing as a constituent of the varied processes that contribute to the development of organizational knowledge. Results. The overall analysis has allowed us to explain how and why organizational information sharing happens in terms that go beyond the cognitive and descriptive accounts (e.g. Widen-Wulff and Ginman, 2004; Widen-Wulff and Davenport, 2005; ; Widen-Wulff, 2006) of our earlier studies. Conclusion. . Information behaviour is a repertoire of actions and operations and judgements about timing and ethics that are brought into play across work cycles and routines. From this perspective, the duality of organizational knowledge becomes clear: it is both individual and collective judgements about how to behave, and the incremental outcome of these judgements, embedded in decisions that support the objects of activity systems.